SIMULASI PENERAPAN PP 71 TAHUN 2010 PADA PENYAJIAN LAPORAN KEUANGAN DAERAH DINAS PETERNAKAN DAN KESEHATAN HEWAN PROPINSI KALIMANTAN BARAT - B51111177, Nurita (Jurnal KIAFE, 2014)
This research was conducted in Dinas Peternakan dan Kesehatan Hewan Propinsi Kalimantan Barat . The primary objective of this study was to perform a simulation application of PP 71 Tahun 2010 on the presentation of financial statements regional Dinas Peternakan dan Kesehatan Hewan Propinsi Kalimantan Barat. This study used a descriptive method , ie a method that describes the object under study beforehand , collect data and make conclusions . Data collection techniques in this study that includes direct observation techniques , interviewing techniques , and library research techniques . The data analysis in this study using qualitative data. . Application of PP 71 Tahun 2010 will be fully implemented in 2015 , so it needs to be done to accelerate the understanding of simulation knowledge of the implementation of the Regional Financial Statements comprehensively how each of the reporting entity to adjust the accrual to the cash -based to one based on future accrual . The results of this study concluded that Dinas Peternakan dan Kesehatan Hewan Propinsi Kalimantan Barat is ready to carry out the application of PP 71 Tahun 2010 which will commence in 2014, to reach the target unqualified assessment.